THE EFFECT ESG DISCLOSURE ON FIRM VALUE: THE MEDIATING ROLE OF FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE 2020–2024 PERIOD - Julia; Keulana Erwin; Rina Br. Bukit (PT. Radja Intercontinental Publishing, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on firm value, with financial performance serving as a mediating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Firm value is proxied by Tobin’s Q, while financial performance is measured using Return on Assets (ROA). The study employs panel data from manufacturing companies during the 2020–2024 period and uses the Bloomberg ESG Disclosure Score as a proxy for ESG disclosure. Data were analyzed using panel data regression and the Sobel test with the assistance of EViews 13 software to examine the mediating effect of financial performance. The results of the main analysis indicate that ESG disclosure does not significantly affect firm value. In addition, although ESG disclosure significantly affects ROA, the direction of the relationship is contrary to the proposed hypothesis. Furthermore, ROA does not significantly affect firm value and is unable to mediate the relationship between ESG disclosure and firm value. However, the robustness test using a one-year time-lag approach reveals that ESG disclosure has a positive and significant effect on both ROA and Tobin’s Q in the subsequent period. The Sobel test further confirms that ROA partially mediates the relationship between ESG disclosure and firm value under the time-lag model. These findings suggest that the benefits of ESG implementation in manufacturing companies are not immediately reflected in financial performance and firm value. Instead, the positive impact of ESG tends to emerge over time, indicating the presence of a time-lag effect. Therefore, ESG should be viewed as a long-term strategic investment capable of creating sustainable value for firms.